Innovations in Islamic Education Management: A Case Study of Vocational High School in Jambi City - Anto, Budi; Us, Kasful Anwar; Shalahudin, Shalahudin (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2024)
This study aims to identify and analyze innovations in Islamic education management at SMK Muhammadiyah Kota Jambi to address the challenges of globalization. Using a qualitative approach, data were collected through in-depth interviews, participatory observations, and document analysis. Findings reveal that innovations were implemented through the integration of Islamic values into vocational curricula, the use of digital technology in management and teaching, and visionary leadership fostering multi-stakeholder collaboration. The integration of Islamic project-based curricula enhanced students' motivation and equipped them with both technical skills and strong Islamic values. Technological advancements improved administrative efficiency and facilitated interactive learning. Visionary leadership played a crucial role in building partnerships with industries and government, contributing to resource enhancement and skill training. These findings highlight the importance of a holistic and adaptive approach to Islamic education management, ensuring graduates are technically competent and morally grounded to meet contemporary demands. This study emphasizes the strategic role of innovation in maintaining the relevance and sustainability of Islamic education institutions.